Evaluation of Vibradiofotology Technology using the ERECTOFIX Device in the Treatment of Erectile Dysfunction: A Randomized Controlled Double-Blind Pilot Study: Evaluation of vibradiofotology technology in erectile dysfunction treatment - Razzaghi, Mohammadreza; Fallah karkan, Morteza; Rahnama, Hossein; Razzaghi, Zahra; Rahnamay Farnood, Parnia (Journal of Lasers in Medical Sciences, 2025)
Introduction: Over the past decade, energy-based therapies have been introduced as noninvasive and restorative treatment modalities for erectile dysfunction. Furthermore, previous studies have shown the efficacy of penile vibratory stimulation and photobiomodulation in treating erectile dysfunction. Integrating these therapeutic approaches, which are employed simultaneously in the Vibradiofotology technology, may lead to achieving better outcomes in the treatment of erectile dysfunction. This study aims to evaluate the efficacy of Vibradiofotology technology delivered via the Erectofix device in patients with erectile dysfunction. Methods: In this randomized clinical trial, fifty-five patients diagnosed with erectile dysfunction were included. The patients were assigned to either the control group or the intervention group. In the intervention group, the patients received treatment with the Erectofix device for five sessions. Each session lasted 45 minutes and was administered once a week. Meanwhile, the control group received oral medication along with sham laser treatment. Results: Among the fifty-five patients included in the study, 27 were assigned to the intervention group and 28 to the control group. The intervention group showed a significant improvement in each domain of the IIEF score compared to the control group. The erectile function showed a significantly greater increase in IIEF scores in the intervention group (19.59±5.57) compared to the control group (7.39±2.23; P<0.001). Furthermore, significant improvements were observed in orgasmic function, sexual desire, intercourse satisfaction, and overall satisfaction in the intervention group. Conclusion: Vibradiofotology technology, which integrates different therapeutic approaches, may be a safe treatment option for erectile dysfunction. Improvements in IIEF scores, patients’ overall satisfaction, and erectile function can be promising in the efficacy of this modality. Nevertheless, due to the limitations of the present study, further research is required to investigate the potential benefits of this novel modality in improving patients’ quality of life.